Effect of bait density on consumption rates and mortality of subterranean termite Coptotermes curvignathus - Yuliati Indrayani; Dewi Fatmawati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2019)
Utilization of baits for controlling termites is achieving high attention in recent year. One of affecting factors of baiting preference of termites including the density of bait. In this study, the effect of bait density on consumption rates and mortality of subterranean termite Coptotermes curvignathus was investigated. Baits prepared by 1:1:1 weight ratio of mixed blended official waste paper, cardboards and cajuput (Melaleuca leucadendra) leaf which were formed into a cube measuring 2x2x1 cm. The baits density were 0.5, 0.6, 0.7, 0.75, 0.8, 1.0 gr/cm3. No choice and multiple choice tests were conducted with five replications. Clear plastics cup measuring diameter 6 cm and 12 cm were employed for no choice test and multiple choice tests respectively. Fifty workers and five soldiers of C. curvignathus were used for no choice test, while 150 workers and 15 soldiers were tested in the multiple choices test. The results indicated that bait with lower density had a better consumption rates to C. curvignathus. The influence of bait density on termite mortality was also reported, since there is a relationship between consumption rates and termite mortality which is contrary to the general toxicity test. The percentage of consumption rates was still lower therefore further research is indispensible on reformulation of the baits.